Know yourself better in and through peer disagreement - Kraft, James Joseph (The University of Edinburgh, 2023)
I aim to answer the following question in this dissertation: How far can one trust claims to self-knowledge based on privileged access in epistemic peer disagreements where those claims are the focus of the disagreement? The answer to this question is contained in the following Assessment Framework: In a peer disagreement where the privileged self-knowledge claim of one disputant is crucially consequential for the disagreement, trust the claim prima facie only if there are no or little significant signs of “judgmental awareness” and/or of observational evidence that implies the claim is questionable; and adjust credence in the privileged self-knowledge claim according to the following scale of such significance: No signs = highest credence; little signs = high credence; significant signs = low credence; highest signs = lowest credence. This Assessment Framework is derived both from six crucial components (numbered in parenthesis below) of peer disagreements about privileged self-knowledge claims discussed throughout the chapters. I begin by arguing, based on empirical research, that both the observational-interpretive method for knowing oneself (component 1) and the privileged access method (2) are needed, and they work together as integrated with mindfulness (3) to form more reliable privileged self-knowledge claims. We show how scholars of peer disagreements make mistakes by not seeing how privileged self-knowledge claims are fragile (4). The remaining crucial components are the Prima Facie Norm (5), which says we should accept prima facie a privileged claim, and the Indirect Scrutability Norm (6) which says that the privileged claim can be scrutinized indirectly by the observational-interpretive method. The culminating sixth chapter derives the Assessment Framework from the six key factors, on one hand, and tests the Assessment Framework against four case studies given, on the other hand. The measure of the success of this framework is how well it naturally accounts for ordinary lived experiences. With the Assessment Framework the person with the privileged self-knowledge claim and the person critical of the privileged claim complete the expanded Delphic maxim Know Yourself (γνῶθι σεαυτόν) better in peer disagreements. Through the process of specifying how to better know yourself in peer disagreements you learn that humans need both ways of knowing yourself, that you need the feedback of others to help you make sure your mental states are what you think they are, that you can know yourself better through mindfulness, and that peer disagreements about privileged self-knowledge claims have value in that they are one of the best ways to deeply Know Yourself. So, the Delphic maxim used also by Socrates and Plato is extended to come to the following: Know Yourself (γνῶθι σεαυτόν) better in and through peer disagreements about privileged self-knowledge claims with mindfulness both in privileged and observational-interpretive access integrated.
Keywords: self-knowledge; epistemic peer disagreements; Prima Facie Norm; Indirect Scrutability Norm; Delphic maxim Know Yourself; privileged self-knowledge; mindfulness